Prevalence of beliefs about actual and mythical causes of cancer and their association with socio-demographic and health-related characteristics: Findings from a cross-sectional survey in England - Shahab, Lion (Eur J Cancer, 2018)
BACKGROUND: Literature on population awareness about actual causes of cancer is growing but comparatively little is known about the prevalence of people's belief concerning mythical causes of cancer. This study aimed to estimate the prevalence of these beliefs and their association with socio-demographic characteristics and health behaviours. METHODS: A survey containing validated measures of beliefs about actual and mythical cancer causes and health behaviours (smoking, alcohol consumption, physical activity, fruit and vegetable consumption, overweight) was administered to a representative English population sample (N = 1330). RESULTS: Awareness of actual causes of cancer (52% accurately identified; 95% confidence interval [CI] 51–54) was greater than awareness of mythical cancer causes (36% accurately identified; 95% CI 34–37; P < 0.01). The most commonly endorsed mythical cancer causes were exposure to stress (43%; 95% CI 40–45), food additives (42%; 95% CI 39–44) and non-ionizing electromagnetic frequencies (35%; 95% CI 33–38). In adjusted analysis, greater awareness of actual and mythical cancer causes was independently associated with younger age, higher social grade, being white and having post-16 qualifications. Awareness of actual but not mythical cancer causes was associated with not smoking and eating sufficient fruit and vegetables. CONCLUSIONS: Awareness of actual and mythical cancer causes is poor in the general population. Only knowledge of established risk factors is associated with adherence to behavioural recommendations for reducing cancer risk.